FOOTBALL FANS' EXPECTATIONS IN INTERPRETING INFORMATION ON TVRI AS THE BROADCASTING RIGHTS HOLDER FOR THE 2026 FIFA WORLD CUP IN THE CONTEXT OF INTRAPERSONAL COMMUNICATION - Juniaty Manullang; Lusiana Andriani Lubis; Nurbani Nurbani (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
This study aims to analyze the characteristics of football fans in Medan City, the views of football fans toward TVRI before obtaining the FIFA World Cup 2026 broadcasting rights, and the expectations of football fans toward TVRI as the holder of the FIFA World Cup 2026 broadcasting rights in the context of intrapersonal communication. This study employed a qualitative method with a constructivist paradigm and a descriptive exploratory approach. Data collection techniques were conducted through in-depth interviews, observation, and documentation involving football fans in Medan City selected using purposive sampling.The results show that football fans in Medan City access football content more frequently through social media, streaming platforms, and collective watching activities rather than conventional television. Before obtaining the FIFA World Cup 2026 broadcasting rights, TVRI was perceived as less modern, less attractive, and lagging behind private television stations and digital media. However, TVRI was still considered to have advantages in providing free access and broad coverage for the public. The expectations of football fans toward TVRI were formed through intrapersonal communication processes influenced by media experiences, personal perceptions, and hopes for improving broadcast quality. Football fans expect TVRI to provide modern, stable, easily accessible broadcasts and to compete with other media platforms in broadcasting the FIFA World Cup 2026.